2022
DOI: 10.1101/2022.03.11.22272276
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factors for SARS-CoV-2 infection after primary vaccination with ChAdOx1 nCoV-19 or BNT1262b2 and after booster vaccination with BNT1262b2 or mRNA-1273: a population-based cohort study (COVIDENCE UK)

Abstract: Background: Little is known about the relative influence of demographic, behavioural, and vaccine-related factors on risk of post-vaccination SARS-CoV-2 infection. We aimed to identify risk factors for SARS-CoV-2 infection after primary and booster vaccinations. Methods: We undertook a prospective population-based study in UK adults (≥16 years) vaccinated against SARS-CoV-2, including data from Jan 12, 2021, to Feb 21, 2022. We modelled risk of post-vaccination SARS-CoV-2 infection separately for participants… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…We think that the risk factors discussed within this paper are unlikely to be greatly affected by a change in the risk of infection in new variants and remain broadly generalisable as risk factors for HCW infection, although the widespread introduction of both population and HCW vaccination since this study is likely to have had a significant impact on these risk factors. 47 Our work identified a number of targetable risk factors for mitigation of the risk of HCW infection during the ongoing COVID-19 pandemic. Maintaining vigilance and providing adequate social distancing space for shift change handover are likely to reduce the risk of HCW infection.…”
Section: Discussionmentioning
confidence: 99%
“…We think that the risk factors discussed within this paper are unlikely to be greatly affected by a change in the risk of infection in new variants and remain broadly generalisable as risk factors for HCW infection, although the widespread introduction of both population and HCW vaccination since this study is likely to have had a significant impact on these risk factors. 47 Our work identified a number of targetable risk factors for mitigation of the risk of HCW infection during the ongoing COVID-19 pandemic. Maintaining vigilance and providing adequate social distancing space for shift change handover are likely to reduce the risk of HCW infection.…”
Section: Discussionmentioning
confidence: 99%
“…Full details of study design have been reported previously. [10][11][12][13] Briefly, from 1st May 2020 to 6th October 2021, UK residents aged ≥16 years were invited via a national media campaign to complete a detailed online baseline questionnaire capturing self-reported information relating to their socio-demographic characteristics, occupation, lifestyle, quality of life, weight, height, longstanding medical conditions, medication use, vaccination status, diet and supplemental micronutrient intake. Follow-up on-line questionnaires capturing behaviours potentially influencing risk of acquiring or transmitting ARI, incident ARI symptoms, results of reverse transcription polymerase chain reaction (RT-PCR) and antigen testing for respiratory viruses, incident exacerbations of asthma and chronic obstructive pulmonary disease and doses of SARS-CoV-2 vaccine received were completed at monthly intervals.…”
Section: Study Design and Setting And Approvalsmentioning
confidence: 99%
“… 2 As a result, even some infected vaccinated patients still have an associated risk of significant morbidity and even mortality related to this viral infection. 3 It is thus urgent to understand the biological mechanisms underlying this disease and to discover alternative or novel therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…However, even though vaccination plans are now used all over the world, several factors, such as the slow pace of vaccination, the fraction of the population that does not develop immunity upon vaccination, and the very good but not total efficiency of vaccines in preventing infection, result in a high number of daily cases, for which effective drug treatment is still lacking . As a result, even some infected vaccinated patients still have an associated risk of significant morbidity and even mortality related to this viral infection . It is thus urgent to understand the biological mechanisms underlying this disease and to discover alternative or novel therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation